Optimizing Maqasid Syariʿah in Sharia Banking Law: A Philosophical Perspective on Islamic Economics - Regita, Ria; Huda, Qomarul; Mu'allifin, Darin Arif (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2024)
This research looks at Sharia banking rules from the point of view of Sharia economic philosophy. It focuses on the ideas of maqāid syarīʿah, which are the main goals or principles of Islamic law that are meant to improve people's lives and make things fair. The study employs a mixed-method approach, integrating normative legal analysis with the maqāṣid syarīʿah framework as defined by classical and modern Islamic thinkers. A lot of primary and secondary sources were looked at to get the information. These included fiqh books, academic journals, and scholarly articles about the rules of maqāid syarīʿah and how the law works. The findings indicate that the implementation of maqāṣid syarīʿah in legal evolution transcends mere compliance with religious duties. It encompasses safeguarding five essential aims (dharuriyyat): religion, life, intellect, lineage, and property. The research illustrates that laws derived from maqāṣid syarīʿah not only guarantee lasting justice but also display adaptability to societal changes while maintaining the fundamental principles of Islamic law. This research adopts an interdisciplinary approach that connects ancient Islamic jurisprudence with modern legal concerns, especially within the Sharia banking sector. The paper gives a new perspective on how Islamic legal principles can help make Sharia banking rules that are flexible and can be used by everyone by basing its research on maqāid syarīʿah. What this shows is that maqāid syarīʿah can improve modern legal systems by combining Islamic values with basic human rights to create a more dynamic and fair financial system.